Cosmic acceleration from second order gauge gravity - Cuzinatto, R. R.; de Melo, C. A. M. [UNESP]; Medeiros, L. G.; Pompeia, P. J. (Springer, 2011)
We construct a phenomenological theory of gravitation based on a second order gauge formulation for the Lorentz group. The model presents a long-range modification for the gravitational field leading to a cosmological model provided with an accelerated expansion at recent times. We estimate the model parameters using observational data and verify that our estimative for the age of the Universe is of the same magnitude than the one predicted by the standard model. The transition from the decelerated expansion regime to the accelerated one occurs recently (at similar to 9.3 Gyr).
Keywords: Cosmic acceleration; Higher order derivative; Gauge theory